Ekspresi Mental Illnes Sebagai Sumber Ide Penciptaan Seni Lukis - Wahana, Karang Sweta; Gunawan, I Wayan; Kondra, I Wayan (Program Studi Seni Murni ISI Bali, 2021)
Mental Illness is a mental disorder that affects thoughts, feelings, and behaviors that are contrary to social norms. Mental illness can be caused by various factors such as genetics, environmental influences and caused by the influence of drugs and illegal drugs. In this influence also causes various effects that can completely affect the character of the sufferer and cause different stimuli according to the mental illness suffered. The different expressions of these stimuli tend to have a dark impression and also give an atmosphere of sadness that surrounds them, these different expressions are chosen by the author as a source of ideas in the creation of painting, with the intention that later this work can also express visually from the sufferer's perspective. mental disorders so as to add insight to the general public. This creation is done through a literature review and aesthetic experience found after direct observation. In the process of creation, this is done by making a rough sketch as a design which will later be used as the initial basis for creation into a painting.